Pengaruh Pergantian Manajemen, Kesulitan Keuangan, Fee Audit, Opini Akuntan dan Ukuran Kap Terhadap Audit Changes - Reni Yendrawati (Unisia, 2011)
The number of public accountant firms increasing may result in commpetition between public accountant firms. In such condition, a corporation may change the auditor. The purpose of this research is to know whether the change of management, financial distress, audit fee, accountant opinion and public accountant firm's size may influence limited corporations in indonesia to change auditors. The data being used is form manufacturing company which is listed in Indonesia Capital Market in 2007 - 2010 periods. The data is analyzed with logistic regression. This research resuit in audit fee and public accountant firm's size as variables influencing auditor changes of accountant opinion, financial distress and change of management as variables not influencing auditor changes.Keywords: auditor changes, change of management, financial distress, audit fee and accountant opinion